IMPACT OF RETROFLEXED VIEW ON THE DETECTION OF LESIONS IN THE PROXIMAL COLON: ASSESSMENT OF 393 PATIENTS IN A PRIVATE TERTIARY HOSPITAL - MADUREIRA,Camila Marques (2021)
ABSTRACT BACKGROUND: The gold standard test for colorectal cancer screening the colonoscopy. Although this is the test of choice, colonoscopy misses a significant number of lesions, mainly in the proximal colon. With the purpose of reducing the number of lesions missed, new techniques have been studied, amongst them, retroflexed view in the right side of the colon and the second direct forward view. OBJECTIVE: Assessing the safety of the retroview in the proximal colon (cecum and ascending colon), its impact on the detection of lesions in the proximal colon and its advantage over the double right forward view using adenoma detection rate and adenoma miss rate. METHODS: Three hundred and ninety-three patients who came to Hospital Mater Dei to undergo colonoscopy from March to July 2017, prospectively. Out of these, 372 were included in the study based on the following exclusion criteria: being under 18 years of age, inadequate bowel preparations (Boston scale <7), history of colectomy, inflammatory bowel disease or polypoid diseases. First, an endoscopist inserted the colonoscope into the cecum and examine the cecum and the ascending colon with a forward view twice. In the third insertion into the cecum, retroflexed view was performed, cecal mucosa was examined until the hepatic flexure in search of polyps missed on forward view. All lesions found were resected and sent for histological analysis. RESULTS: In 334 (89.8%) patients, retroflexed view was performed successfully, 65.8% of failures were attributed to the loops of the device which prevented the maneuver. The direct view identified 175 polyps in the proximal colon in 102 people. Retroflexed view detected 26 polyps missed by the direct view in 24 (6.5%) people, with a missing rate of 12.9% in the test with only the forward view. Out of the 26 polyps found in retroview, 21 (80.76%) were adenomas, one of them with a high-grade dysplasia. Eleven patients had polyps seen only in retroflexed view. Retroview has increased the polyp detection rate from 27.41% to 31.72% and the adenoma detection rate from 21.77% to 25%. The adenoma miss rate by the double direct view was 12.8%. Without the retroview, one polyp in every 13.91 colonoscopies would be missed (number needed to treat - NNT=13.91). There was no adverse event. CONCLUSION: The retroflexed view technique in the proximal colon was shown to be safe, fast and feasible in most cases. It increased the adenoma detection rate and was shown to be advantageous in this study wit benefit beyond the double direct view.